2021
DOI: 10.1371/journal.pntd.0009162
|View full text |Cite
|
Sign up to set email alerts
|

Developmental outcomes in children exposed to Zika virus in utero from a Brazilian urban slum cohort study

Abstract: Background The prevalence of developmental alterations associated with in-utero Zika virus (ZIKV) exposure in children is not well understood. Furthermore, estimation of the Population Attributable Fraction (PAF) of developmental alterations attributed to ZIKV has not been performed due to lack of population-based cohorts with data on symptomatic and asymptomatic ZIKV exposures and an appropriate control group. The aim of this study was to characterize neurodevelopmental outcomes of children at 11 to 32 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 30 publications
3
30
0
2
Order By: Relevance
“…Our overall results are consistent with another Brazilian study, which analyzed a smaller sample and reported a difference between groups concerning the cognitive domain but not for the motor and language domains [ 8 ]. Pursuing a more detailed comparison between groups, we analyzed the outcomes of the BSIDIII subtests using balanced scores for receptive and expressive communication as well as gross and fine Motor; the frequency of delays in these subtests did not differ significantly between the exposed and unexposed groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our overall results are consistent with another Brazilian study, which analyzed a smaller sample and reported a difference between groups concerning the cognitive domain but not for the motor and language domains [ 8 ]. Pursuing a more detailed comparison between groups, we analyzed the outcomes of the BSIDIII subtests using balanced scores for receptive and expressive communication as well as gross and fine Motor; the frequency of delays in these subtests did not differ significantly between the exposed and unexposed groups.…”
Section: Discussionsupporting
confidence: 92%
“…The short-term risks of congenital ZIKV infections are already known and the impairment of neurodevelopment is evident in children with moderate to severe microcephaly [ 4 , 5 , 6 ]. However, the risk of developmental delays in children with evidence of maternal ZIKV infection during pregnancy born without microcephaly remains unknown [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recent study of Ticona et al (2021) [ 35 ] investigated the relationship between the in-utero Zika virus exposure and the prevalence of developmental alterations in early childhood. It was observed that from a group of women living in a slum community in Brazil, both the asymptomatic and symptomatic Zika virus infection during the antenatal period is associated with mild neurodevelopmental abnormalities in children asymptomatic at birth.…”
Section: Resultsmentioning
confidence: 99%
“…Of course, microcephaly of any type is considered a major driver of neurology and neurodevelopment delays [ 43 ]. However, the fact that neurodevelopmental and neurological disorders were observed also in children born asymptomatically indicates that the exposed children without CZS appeared at risk for neurodevelopmental disorders in all of the domain disorders, such as motor, cognition, and mainly in language [ 20 , 27 , 32 , 35 ]. Furthermore, normocephalic children should also be under frequent follow-up, due to an increased risk of developing microcephaly after birth [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…[9,10]. Intrauterine exposure to ZIKV can result in Congenital Zika Syndrome (CZS), which includes a range of physical and neurological impairments, such as microcephaly [9][10][11].…”
Section: Introductionmentioning
confidence: 99%